Antibacterial activities of selected Cameroonian spices and their synergistic effects with antibiotics against multidrug-resistant phenotypes - Fankam Aimé G; Kuete Victor; Voukeng Igor K; Kuiate Jules R; Pages Jean-Marie (BMC, 2011)
Abstract Background The emergence of multi-drug resistant (MDR) phenotypes is a major public health problem today in the treatment of bacterial infections. The present study was designed to evaluate the antibacterial activities of the methanol extracts of eleven Cameroonian spices on a panel of twenty nine Gram negative bacteria including MDR strains. Methods The phytochemical analysis of the extracts was carried out by standard tests meanwhile the liquid micro-broth dilution was used for all antimicrobial assays. Results Phytochemical analysis showed the presence of alkaloids, phenols and tannins in all plants extracts. The results of the antibacterial assays indicated that all tested extracts exert antibacterial activities, with the minimum inhibitory concentration (MIC) values varying from 32 to 1024 μg/ml. The extracts from Dichrostachys glomerata, Beilschmiedia cinnamomea, Aframomum citratum, Piper capense, Echinops giganteus, Fagara xanthoxyloïdes and Olax subscorpioïdea were the most active. In the presence of efflux pump inhibitor, PAßN, the activity of the extract from D. glomerata significantly increased on 69.2% of the tested MDR bacteria. At MIC/5, synergistic effects were noted with the extract of D. glomerata on 75% of the tested bacteria for chloramphenicol (CHL), tetracycline (TET) and norfloxacin (NOR). With B. cinnamomea synergy were observed on 62.5% of the studied MDR bacteria with CHL, cefepime (FEP), NOR and ciprofloxacin (CIP) and 75% with erythromycin (ERY). Conclusion The overall results provide information for the possible use of the studied extracts of the spices in the control of bacterial infections involving MDR phenotypes.